Experimental study on the response of mistuned bladed disk [electronic resource] - 252789 Abdelgadir Mohamed Mahmoud; Mohd. Salman Leong, supervisor; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (PhD) - Universiti Teknologi Malaysia, 2006